Inositol polyphosphates and target of rapamycin kinase signalling govern photosystem II protein phosphorylation and photosynthetic function under light stress in Chlamydomonas. Issue 5 (5th October 2021) - Couso, Inmaculada; Smythers, Amanda L.; Ford, Megan M.; Umen, James G.; Crespo, José L.; Hicks, Leslie M.
Summary: Stress and nutrient availability influence cell proliferation through complex intracellular signalling networks. In a previous study it was found that pyro‐inositol polyphosphates (InsP7 and InsP8 ) produced by VIP1 kinase, and target of rapamycin (TOR) kinase signalling interacted synergistically to control cell growth and lipid metabolism in the green alga Chlamydomonas reinhardtii . However, the relationship between InsPs and TOR was not completely elucidated. We used an in vivo assay for TOR activity together with global proteomic and phosphoproteomic analyses to assess differences between wild‐type and vip1‐1 in the presence and absence of rapamycin. We found that TOR signalling is more severely affected by the inhibitor rapamycin in a vip1‐1 mutant compared with wild‐type, indicating that InsP7 and InsP8 produced by VIP1 act independently but also coordinately with TOR. Additionally, among hundreds of differentially phosphorylated peptides detected, an enrichment for photosynthesis‐related proteins was observed, particularly photosystem II proteins. The significance of these results was underscored by the finding that vip1‐1 strains show multiple defects in photosynthetic physiology that were exacerbated under high light conditions. These results suggest a novel role for inositol pyrophosphates and TOR signalling in coordinating photosystem phosphorylation patterns in Chlamydomonas cells in response to light stress and possibly other stresses.